DESAIN MODIFIKASI PERMAINAN TRADISIONAL SEBAGAI ALTERNATIF UNTUK PEMANASAN (Universitas Majalengka, 2021)
The aim of this research is the development of warm-up with traditional games for students before doing sports activities. The method used is Research and Development (RnD) with procedures for potential problem analysis, product design, expert validation, design revision, and testing. The subjects in the study were 10 students of Sports Coaching Education, from 7 sons and 3 daughters with an average age of 20 years. The instrument uses a pulse measuring test and a questionnaire. The analysis technique uses descriptive statistical calculations. The results of the judge's assessment for the first game were 98%, the second game was 98% and the third game was 98%, which means that the assessment of the design was categorized as